Oxygen reduction reaction activity and structural stability of Pt–Au nanoparticles prepared by arc-plasma deposition. Issue 28 (28th July 2015) - Takahashi, Shuntaro; Chiba, Hiroshi; Kato, Takashi; Endo, Shota; Hayashi, Takehiro; Todoroki, Naoto; Wadayama, Toshimasa
<x xml:space="preserve">Abstract</x> Sequential arc-plasma deposited Pt–Au alloy nanoparticles show superior electrochemical structural durability compared with arc-plasma deposited Pt nanoparticles before and after electrochemical potential cycles.